Analysis of Factors Influencing Students' Interest in Continuing Their Studies at Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh - Muliza; M. Aditya Ananda; Indah Zahra; Rika Dara Selviani (Pencerah, 2025)
This research aims to analyze the factors that influence student's interest in Aceh Jaya Regency, West Aceh Regency, and Nagan Raya Regency in continuing their studies at the Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh. The factors studied include Family Environment, Religiosity, Knowledge about STAIN, Career Opportunities, and Promotion. The research method used is a quantitative approach using multiple linear regression analysis. Data was collected through questionnaires distributed to 342 high school, MA and vocational school students who were the research samples. The research results show that the variables Family Environment, Religiosity, Knowledge about STAIN, and Promotion have a significant influence on student interest, while Career Opportunities do not show a significant influence. The coefficient of determination test shows that this model is able to explain 98.7% of variations in student interest. The results of the F test confirm that the overall research model is significant, while the t test strengthens the finding that Promotion has the largest influence among the other variables. Based on the research results, it is recommended that STAIN improve promotional and outreach strategies to students and families, as well as strengthen information about career prospects to attract the interest of more prospective students.